Urgensi Akta Otentik Perkawinan - Fadhilah Bardan (Al-Fikrah, 2022)
This study examines the urgency of the authentic marriage certificate in the Samalanga sub-district. The problems studied are what are the factors that cause many families in Samalanga District not to have a marriage certificate, how is the urgency of a marriage certificate in a marriage according to the maslahah mursalah review. The purpose of this study was to determine the factors causing the number of families in the Samalanga District not to have a marriage certificate. To find out the urgency of this marriage certificate in a marriage, according to Maslahah mursalah's review. The research method in writing this article is qualitative. From the results of the study, it can be concluded that the factor that causes many families in Samalanga District to not have a marriage certificate is that many people carry out unregistered/polygamous marriages without the knowledge of their wives so that they marry without reporting to the KUA and their marriages are not recorded. A secret marriage is carried out because both partners do not have the blessing of both parents, so the marriage does not have a marriage certificate. The urgency of a marriage certificate in a marriage according to the concept of maslahah aims to provide legal certainty and protection for husband and wife, including legal certainty and protection against the consequences that arise from the marriage itself, namely regarding the rights and obligations of each reciprocally, regarding children. Born, and the rights of children in the form of inheritance from their parents later.